Policy Alternatives for Strengthening Small-Scale Public-Private Partnerships in Azerbaijan: Covering Gaps in Effective Public Service Provision in Azerbaijan - Huseynli, Sevilay; Safikhanli, Farida; Miriyeva, Nigar (ADA University, 2025)
Small-Scale Public-Private Partnerships (SSPPPs) are known around the world as effective tools for promoting regional development and making essential services more accessible. However, in Azerbaijan, the adoption of SSPPPs remains limited despite recent legislative efforts aimed at strengthening public-private cooperation. This policy paper examines the key barriers to SSPPP development in local context, mainly focusing on restrictive financial thresholds, complex administrative procedures, and limited institutional capacity. Using qualitative interviews with key public sector representatives involved in local PPPs in a combination with comparative analysis of international best practices, particularly Uzbekistan’s experience, the study identifies practical shortcomings in Azerbaijan’s PPP framework. Findings of the research reveal that while utility power of SSPPPs are recognized worldwide, the current legal and procedural requirements effectively exclude smaller-scale projects, particularly in rural and regional areas. The qualitative research identified rigid financial threshold of 30 million AZN to be the main barrier of entry for majority of small scale projects. The paper concludes by suggesting targeted policy recommendations to address these challenges, including legal adjustments, capacity-building plans, and process streamlining system. By aligning policy frameworks with practical needs on hand, Azerbaijan can better utilize SSPPPs to advance its goals of economic diversification, social equity, and balanced regional development.
Keywords: Public-private sector cooperation -- Azerbaijan.; Regional development -- Government policy -- Azerbaijan.; Public-private partnerships -- Law and legislation -- Azerbaijan.; Infrastructure development -- Government policy -- Azerbaijan.